2015
DOI: 10.3144/expresspolymlett.2015.87
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rubber polarity on selective wetting of carbon nanotubes in ternary blends

Abstract: Carbon nanotubes (CNTs) with special nanoscale structure combined with the high strength of the carbon-carbon bondings and a large aspect ratio opens up a wide range of new applications [1]. However, the physical properties of the CNT-polymer composites are often below expectations, because a sufficiently effective force transfer between the polymer matrix and CNTs has not yet been reached. In order to exploit the exceptional mechanical and electrical properties of CNTs in polymer composites, the filler wettin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Le et al reported that there is a cation‐ pi interaction between the phospholipids in NR and the CNT surfaces. From literature, it can be seen that polymers can wrap around CNTs, forming supramolecular complexes . This can be explained by the wrapping mechanism that attributed to certain specific interactions between the polymer and the CNT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Le et al reported that there is a cation‐ pi interaction between the phospholipids in NR and the CNT surfaces. From literature, it can be seen that polymers can wrap around CNTs, forming supramolecular complexes . This can be explained by the wrapping mechanism that attributed to certain specific interactions between the polymer and the CNT.…”
Section: Resultsmentioning
confidence: 99%
“…MWCNT can act as a compatibilizer in NR/NBR blends. Le et al developed a ternary blend of NR/NBR/SBR using CNT as the filler. They reported that CNT mainly reside in the polar NBR and non‐polar NR than in weak polar SBR.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, in the case of electric vehicle (EV) technology, the tire with low thickness, high durability and electrically conducting are essential. Nowadays, many types of natural rubber (NR) [ 1 ] and synthetic rubber (SR) have been investigated such as styrene-butadiene rubber (SBR) [ 2 ], butadiene rubber (BR) [ 3 ] and their blends including NR/SBR, SBR/BR and NR/BR/SBR [ 4 , 5 , 6 ]. This is attributed to the superior elasticity and flexibility of NR and BR [ 7 , 8 ] along with the SBR which has well rolling properties and wet fraction due to π–π interaction of existing benzene ring in the molecular structure [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increase in bound rubber content with the presence of silane, increasing filler content and mixing time was observed [ 21 , 22 ], when it decreased at high extraction temperatures [ 20 ]. In binary and ternary rubber blend systems, the wetting concept was widely used to identify filler localization and rubber–filler interactions [ 23 , 24 , 25 , 26 ]. The bounded rubber principle lies under the wetting concept as well; however, the calculations are carried out differently from the bound rubber concept.…”
Section: Introductionmentioning
confidence: 99%